Effectiveness of a multicomponent exercise program to reverse pre-frailty in community-dwelling Chinese older adults: a randomised controlled trial. (1st March 2022) - Dun, Yaoshan; Hu, Peng; Ripley-Gonzalez, Jeffrey W; Zhou, Nanjiang; Li, Hui; Zhang, Wenliang; Chen, Meijuan; Zheng, Qingsong; Cui, Ni; Wu, Shaoping; Liu, Suixin
Abstract: Background: the Xiangya Hospital circuit training (X-CircuiT), was developed to reverse pre-frailty in Chinese older adults and determine potential mechanisms through which pre-frailty is reversed. Methods: this randomised controlled trial was performed at Xiangya Hospital, Changsha, China from September 2020 to May 2021. Forty-eight pre-frail older adults were enrolled. Participants were randomly assigned (1:1) to X-CircuiT (46 min/session, three supervised sessions/week for 3 months at a community health centre) or control (1-time advice on physical activity without supervised exercise). The primary outcome was the proportion of participants with pre-frailty after 3-month intervention. The secondary outcomes included absolute risk reduction (ARR), number needed to treat (NNT), and the changes in senior fitness, body composition and clinical measures. Results: among 48 participants (mean age, 72 years; women [65%]), 22 participants in the X-CircuiT (92%) and 21 participants in the control (88%) completed the study. After 3 months, the proportion of pre-frailty was significantly lower in the X-CircuiT group than the control (14% versus 95%, P < 0.001). The ARR and NNT were 82% [95% CI, 65–99] and 1 [1–2], respectively. X-CircuiT was associated with significant improvements in senior fitness indicators and body composition. No significant difference in blood chemistry, carotid ultrasound and echocardiography parameters was found between groups. No significant interaction was detected between sex, BMI, baseline peak oxygen consumption and study groups. Conclusion: this study demonstrates that X-CircuiT could significantly reverse pre-frailty in Chinese older adults. The underlying mechanisms may involve X-CircuiT-induced improvements in body composition and senior fitness. The trial is registered at Chictr.org.cn . Number: ChiCTR2100048125.